اثر ممارسة التدريبات الرياضية اليومية في ظل جائحة كورونا على بعض الاظطربات النفسية لدى صنف الاواسط - بهيليل, اسماعيل; سنوسي, جلال (Institut d’Éducation Physique et Sportive mostaganem 2021/2022, 2021)
The effect of daily sports exercises during the Corona pandemic on some psychological disorders in students at the age of 18 . This study aimed to know the effect of daily exercises during the Corona pandemic on some mental disorders (anxiety and aggression) in the middle class, in the theoretical aspect of this study we talked about the concept of sports exercises and psychological disorders,the students on the age of 18 and the Corona pandemic. For the pratical aspect, the descriptive approach was adopted in a survey method, and the study tool consisted of a three-axis questionnaire directed to a sample of 30 athletes at the age of 18 from the amateur football club in Sidi Bel Abbes. To verify the validity and reliability of the questionnaire and its axis, and finally, after the process of analysis, interpretation and analysis of previous studies and comparing it with the subject of our study, we concluded that daily sports exercises during the Corona pandemic have a positive effect on reducing some psychological disorders in students at the age of 18. Through these results, recommendations and future suggestions were made, most notably: - keeping up with daily sport exercises. -The necessity of continuing sports activities during the Corona pandemic. -Carrying out similar studies in depth about mental disorders in athletes.
LES-2022-7
Keywords: التدريبات الرياضية اليومية - جائحة كورونا - الاظطربات النفسية - صنف الاواسط